Psychological toughness and its relationship to some physical abilities and accuracy of performance of some basic skills among Baghdad University handball team players - Roaa Akbar; Shaima Yassin; Jamal hamza (College of Physical Education and Sport Sciences, 2024)
Research objective Identifying psychological toughness and its relationship to some physical abilities and the accuracy of performing some basic skills among Baghdad University handball team players. As for the search hypothesis It is the existence of a correlation between psychological toughness, physical abilities, and the accuracy of performing some basic skills among the players of the University of Baghdad handball team. The researchers used the descriptive approach in the form of correlational relationships to suit the research problem, as the research population was limited to (18) players for the Baghdad University handball team, while the research sample included (14) players, and the research sample constituted (88%). The research concluded that the University of Baghdad handball team has high psychological toughness and its level of physical and skill performance is good. There is a strong and significant correlation between psychological toughness and the skill and physical performance of the university handball team players. The researchers recommended the need to pay attention to the psychological aspects and develop psychological toughness among the players of the University of Baghdad handball team and other sports in general. Because the study showed the solidity in skill and physical performance and its high score. There is a need to study the relationship of psychological toughness to the performance of other skills in other games.